‘Good Faith’ in Land Transaction: A Comparative Analysis of the USA and Netherlands Law - Karjoko, Lego; Iswantoro; Ramazanova, Makhabbat (Lembaga Contrarius Indonesia, 2024)
The lack of uniformity among judges in interpreting the criteria for buyers' good faith in land sale and purchase cases results in less favorable outcomes for buyers. This study aims to compare the regulations and implementations of the principle of good faith in land transactions in the United States, the Netherlands and Indonesia. Utilizing a statutory and conceptual approach, supplemented by comparative analysis, this research examines the relevant laws and concepts, including contractual rules and regulations governing sales and purchases. The findings indicate that the legal system significantly influences how countries regulate the principle of good faith—either concretely or abstractly. This influence is closely tied to the concepts of written legal sources, jurisprudence, and the practical application of the principle in statutory regulations. Generally, Indonesia, like other countries, faces challenges in implementing the principle of good faith, particularly for buyers, due to the lack of a definitive benchmark to assess whether agreements are executed in good faith and fairness. To address this issue, the regulation of good faith and its criteria should be clearly articulated in written laws. Ensuring that the principle of good faith is applied throughout the entire land buying and selling process—from pre-contractual stages to contract execution—is crucial for providing adequate protection for buyers acting in good faith.